2008
DOI: 10.1016/j.jpeds.2008.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Mass Index in Children with White Coat Hypertension

Abstract: Objective-To determine if children with white coat hypertension (WCH) have evidence of targetorgan damage by comparing left ventricular mass index (LVMI) of subjects with WCH to that of matched normotensive and hypertensive controls.Study design-Each WCH subject was matched by body mass index (± 10%), age (± 1 year), and sex to a normotensive control and to a hypertensive control. Echocardiograms were reviewed to determine LVMI for each subject. These triple matches were analyzed using repeated measures analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 30 publications
4
42
0
1
Order By: Relevance
“…The impact of white coat hypertension on left ventricular function remains controversial. In some studies, increased left ventricular mass in patients with WCH in comparison to healthy controls was reported [5]. In this study no significant differences of shortening and ejection fraction, describing left ventricular systolic function, between analysed groups were found, which is consistent with the majority of reports [13,14,[17][18][19].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The impact of white coat hypertension on left ventricular function remains controversial. In some studies, increased left ventricular mass in patients with WCH in comparison to healthy controls was reported [5]. In this study no significant differences of shortening and ejection fraction, describing left ventricular systolic function, between analysed groups were found, which is consistent with the majority of reports [13,14,[17][18][19].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study LVMI was significantly higher in hypertensive boys than in normotensive ones, while no differences were found between hypertensive and WCH-hypertensive male subgroups as well as between WCH-hypertensive boys and normotensive ones. These results are consistent with data presented in the literature on condition that their authors analysed groups consisting of males and females [13][14][15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A screening study of 5,102 children aged 10-19 years in the Houston public schools demonstrated that 4.5% of children had hypertension, and 11% with BMI greater than or equal to the 95 th percentile had hypertension [3]. A repeat study in the Houston schools of 6,790 adolescents aged [11][12][13][14][15][16][17] showed that 81.1% of children had normal BP, 15.7% had prehypertension, and 3.2% had hypertension [4].…”
mentioning
confidence: 99%
“…In adults, there is evidence that WCH is a non-benign condition with high risk of progression to true hypertension; it is unknown whether this holds true for children with WCH [13,14]. While current guidelines do not recommend a diagnostic workup for children with WCH, this condition may represent an intermediate state between normal blood pressure and hypertension [1,15]. Thus, patients with WCH may benefit from modification of unhealthy lifestyle habits and monitoring for worsening hypertension.…”
mentioning
confidence: 99%